Demographic, Clinical, and Tumor Profile Of Meningioma In Mohammad Hoesin Hospital Palembang, Indonesia - Dya Anggraeni; Yunni Diansari; Zen Hafy (Biomedical Journal of Indonesia, 2022)
Introduction. Meningioma was the most frequently reported primary intracranial tumor. There had been a few reports about meningioma profile in Indonesia. The objective of this study is to identify the profile of meningioma based on demographic, clinical, and tumor characteristics. Methods. This is a cross-sectional study using secondary data from medical records. There were 67 meningioma patients based on histopathological examination at Mohammad Hoesin Hospital  from January to December 2018. Various data were recorded, including demografic profile,  history of hormonal contraceptive use, neurologic symptoms, and tumor characteristic. Results. During 2018, the incidence of meningioma was 68,3% of all primary CNS tumors. Meningioma was mostly found in the age group 35-44 years (44.8%). Most of the patients was female (92.5%) and 29 patients (46.8%) had a history of hormonal contraceptive use. Headache showed the highest rate of clinical manifestation in meningioma patient (34.3%). Based on the location, convexity meningioma was the most frequently found (65.7%). Of the 67 meningioma patients, only 26 datas were obtained regarding a history of radiation exposure and all without a history of radiation. There was only one patient (1.5%) with a family history of malignancy (breast tumor). Based on histopathological examination, 60 patients (89.6%) reported as WHO grade I, mostly the meningothelial subtype (40%). The outcome was generally good in most patients (88.1%). Conclusion. In our institution, meningioma is the most commonly found primary brain tumor. Headache was the most common clinical manifestation and these tumors were mostly located in convexity of the brain, with the majority being WHO grade I and meningothelial subtype.